I-SCC Behavior Evaluation of N36 Zirconium Alloy Cladding Using Ring Tensile Test. Issue 1 (January 2015) - Meng, Yan; Qiwei, Yin; Pengfei, Wang; bo, Liang; Meiling, Wang
Abstract A ring tensile test was performed to study the iodine-induced stress corrosion cracking (I-SCC) behavior of N36 zirconium alloy cladding at 350°C and in 102, 103, 104 Pa iodine vapor pressures. Morphologies of ring samples were observed by optical microscope, ring tensile load-displacement curves and parameters were analyzed to evaluate I-SCC susceptibility. The fracture surfaces of samples after test show the brittle fracture in iodine vapor which is different from cup-cup ductile fracture with non-iodine. Load-displacement curves and parameters show that the mechanical properties are degraded in iodine vapor environment compared to that in non-iodine environment, and more significantly decrease when increasing iodine content. Cladding tube toughness is considered to be an appropriate parameter to assess the I-SCC susceptibility; as a result, cladding toughness decreases gradually with the increasing of iodine content.